ANIMAL INSURANCE OF CATTLE/BOW IN INDONESIA: REGULATION, MECHANISM AND RESPONSIBILITY - Yana Listiyani (Progressive Law Review, 2022)
Running a livestock business may pose risks such as death of animals due to death, accidents, loss/theft, natural disasters including disease outbreaks and price fluctuations. Any potential risks must be minimized to avoid losses. If the farmer cannot prevent or face the risk, he will experience a loss. Risks in cattle/buffalo farming include management, production, human resources, price, finance, loss and death risks that can cause losses. Cattle/buffalo animal insurance is included in the type of agricultural insurance regulated in the law. Number 19 of 2013 concerning Protection and Empowerment of Farmers, but still referring to the Law of the Republic of Indonesia number 40 of 2014 concerning insurance, the AUTS Program is a type of loss insurance. As an agreement between the insurer (insurance company) and the insured (cow breeder) it must be subject to the provisions of the KUHD and the Civil Code. The guidelines set out in implementing AUTS are in accordance with the provisions of insurance law, starting from the provisions of the agreement between the insurer and the insured, the object being insured, the premium to be paid by the insured, the provisions of the insurance policy made and signed by each party, to the mechanism for submitting a claim.